Pengembangan LKPD Berbasis PBL Bernuansa Etnomatematika di Istana Maimun - Cici Wulandari Sitorus; Fitriani Fitriani; Lilis Suryani Nasution; Mayang Nabila; Nurul Fatma Dewi Mardianto; Sarmila Fitri Yanti Nasution; Ella Andhany (Lembag, 2025)
Ethnomathematics is one of the approaches that integrates local wisdom with mathematics learning. This study aims to develop PBL-based LKPD with ethnomathematics nuances at the Maimun Palace. This research method is research and development (Research and Development). The development model used as the basis for this study is the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The results of the study showed that the LKPD developed was included in the valid category, for the average overall result of the LKPD validation assessment from the three validators was 4.35. In the implementation, the response of students to the LKPD with an average score of 4.48 was categorized as very good and met the practicality of the LKPD, so it did not need to be revised again. The PBL-based LKPD with ethnomathematics nuances produced, along with its supporting instruments, have met the criteria of validity, practicality, and effectiveness.